Yuan Ethnic’s Greeting Expressions in Pakvaid Village, Xiengneun District Luangphabang Province - SIRIKOUN, Somphet (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research has studied on the Study of Yuan’s ethnic Greeting, in Parkvaed Village, Xieng Ngern District, Louang Prabang Province, it is a quality study with two purposes include manner of greetings of Yuan’s ethnic in the society and using the theories of (KALAYA and AMMALA 1998) and studied on the species of greeting sentence, according to the purpose of the speech and using the theories of (Boualy PAPHAPHAN 2002). The information gathered to study at this time is coming from the conversation recorded of Yuan people in their life of living The studied has found that the analysis on the manner of greetings of Yuan’s ethnic has changed in social factors in relationship that is not equal included the relationship of the speakers have higher status than the listeners and the speakers have lower status than the listeners. And has changed on the relationship with equal included the greeting on the various situation. The studied-on species of greeting sentence according to the purpose of all speeches that show of 4 sentence species, there are include the greeting in the simple sentences, question sentences, dictatesentences, interjection sentences. The first of using in the greeting include dictate sentences with the total of 23 cases, the second one that question sentences with the total of 16 cases, and simple sentences is the least one to use only 3 cases.